1996
DOI: 10.1183/09031936.96.09020301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro and in vivo administration of dexamethasone on rat macrophage functions: comparison between alveolar and peritoneal macrophages

Abstract: Resident alveolar macrophages (AMs) and peritoneal macrophages (PMs), though they originate from common precursor cells, differ morphologically and functionally. The two types of macrophages residing in different tissues may respond differently to glucocorticoids.In the present study, we compared the effects of a synthetic glucocorticoid, dexamethasone (Dex), on rat AMs and PMs with regard to their phagocytic activity and tumour necrosis factor-α (TNF-α) releasability.In vitro exposure of the macrophages to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
1
21
2
Order By: Relevance
“…The results showed that dexamethasone had no effect on the phagocytic activity of alveolar macrophages. This observation is contradictory to the previous report of Nakamura et al in that dexamethasone was found to suppress the phagocytic activity of alveolar macrophages in their study (36). A careful comparison of the immunosuppression protocols revealed that Nakamura et al used 4 to 50 times more dexamethasone (1.25 to 20 mg/kg/day) than we did in the present study, in which rats were immunosuppressed with 0.36 mg/kg/day.…”
Section: Discussioncontrasting
confidence: 56%
“…The results showed that dexamethasone had no effect on the phagocytic activity of alveolar macrophages. This observation is contradictory to the previous report of Nakamura et al in that dexamethasone was found to suppress the phagocytic activity of alveolar macrophages in their study (36). A careful comparison of the immunosuppression protocols revealed that Nakamura et al used 4 to 50 times more dexamethasone (1.25 to 20 mg/kg/day) than we did in the present study, in which rats were immunosuppressed with 0.36 mg/kg/day.…”
Section: Discussioncontrasting
confidence: 56%
“…It decreases the numbers of MHC class II cells in chickens (Isobe and Lillehoj, 1993) and reduces the immunostimulatory capacity of dendritic cells in mammals (Lim et al, 1996). Numerous in vitro studies have shown that dexamethasone inhibits the production of certain immune cytokines by macrophages and microglia (e.g., Ganter et al, 1992;Nakamura et al, 1996). Dexamethasone inhibits macrophage activation and cytokine production in mammals and birds (e.g., Russo-Marie, 1992;Corrier et al, 1991;Isobe and Lillehoj, 1992;Hubner et al, 1996).…”
Section: Benefits Of Leukocyte Subtype Identification In Inner Ear Sementioning
confidence: 97%
“…After incubation for 48 or 72 h with calcitriol, the cells were plated in a 24-well plate at 10 6 cells/0.9 ml/well, and 0.1 ml of endotoxin at various concentrations was added to each well. The cell suspensions were incubated for 17 h at 37°C, and then the supernatants were assayed for TNF-␣ by a cytotoxicity assay with L929 cells (obtained from Japanese Cancer Research Resources Bank-Cell) as previously described (22).…”
Section: Methodsmentioning
confidence: 99%